2005
DOI: 10.4161/cc.5.2.2361
|View full text |Cite
|
Sign up to set email alerts
|

Connecting p63 to Cellular Proliferation: The Example of the Adenosine Deaminase Target Gene

Abstract: An unresolved issue regards the role of p73 and p63, the two homologs of the p53 oncosuppressor gene, in normal cells and in tumor development. Specific target genes for each protein need to be identified and characterized in order to understand the specific role of each protein in tumor initiation and progression as well as in oncosuppression and development. We tested whether p63 is implicated in transcriptional events related to sustaining cell proliferation by transactivation of antiapoptotic and cell surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Consistent with this observation, a positive effect on cell proliferation has been previously reported in human keratinocytes (Sbisa et al 2006;Truong et al 2006) and in zebrafish epidermis (Lee and Kimelman 2002).…”
Section: ‫4מ‬supporting
confidence: 77%
“…Consistent with this observation, a positive effect on cell proliferation has been previously reported in human keratinocytes (Sbisa et al 2006;Truong et al 2006) and in zebrafish epidermis (Lee and Kimelman 2002).…”
Section: ‫4מ‬supporting
confidence: 77%
“…1 and 2A and B), they should differentially regulate the subset of G 1 -S and S phase target genes analyzed. Indeed, we previously showed that ADA and FASN are direct p73 and p63, but not p53, target genes (11,12,14). To test the ability of the different p53 family members to regulate the ADA, FASN, POLD2, CCND3, CDC25C, and CDC2 promoters, we performed transactivation assays.…”
Section: Resultsmentioning
confidence: 99%
“…MCF-7 cells were lysed and extracted as previously described (11). For immunoblotting, the following primary antibodies were used: p53 DO-1 (1:300; Santa Cruz Biotechnology), p53-pAb1801 (1:100; Santa Cruz Biotechnology), p63 antibody 4A4…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…p73 is a member of the p53 family of transcription factors, and it shares many characteristics with its famous cousin (reviewed in refs. [11][12][13][14][15]. It is able to recognize the same consensus sequences on many promoters of genes induced by wild-type p53, which lead to the accumulation of proteins involved in cell cycle arrest, senescence or apoptosis.…”
Section: One Of the Most Important Partners Has A Pro-apoptotic Functmentioning
confidence: 99%